DNA mediated assembly of quantum dot–protoporphyrin IX FRET probes and the effect of FRET efficiency on ROS generation1. Issue 8 (28th February 2015) - Singh, Seema; Chakraborty, Anirban; Singh, Vandana; Molla, Aniruddha; Hussain, Sahid; Singh, Manoj K.; Das, Prolay
<x xml:space="preserve">Abstract</x> Quantum dot-protoporphyrin IX FRET probes are assembled through DNA hybridization and the efficiency of FRET and ROS generation was studied.